HEADACHES AFTER SPINAL ANESTHESIA AND THEIR LINK WITH RELATED FACTORS IN CANDIDATES FOR CESAREAN - Kamel Abdi; Mehrdad Abdullahzadeh; Behzad Gholamveisi; Hatam Aghabakpour; Aram Karimian (Nurse and Holistic Care, 2024)
Background: During a cesarean section, spinal anesthesia can result in post-dural puncture headaches. Objective: A group of female candidates for cesarean was studied to explore the link between post-spinal anesthesia headaches and factors, including age, BMI, blood pressure, fasting blood sugar, duration of immobilization in the supine position after spinal anesthesia, and history of prior spinal anesthesia and post-dural puncture headache. The needle size, type, and technique used for spinal anesthesia remained constant throughout the study. Methods: A cohort study was conducted on 80 women who were scheduled to undergo cesarean sections at a hospital in Iran. Researchers used the numeric pain rating scale to assess the severity of the women's headaches following spinal anesthesia. Through t-tests and chi-square tests, the potential link between headaches and related factors was analyzed. Result: The researchers found no significant association between headaches and factors such as age, BMI, blood pressure, fasting blood sugar, duration of immobilization in the supine position after spinal anesthesia, and history of prior spinal anesthesia and post-dural puncture headache (P > 0.5). Conclusion: When performing cesarean sections, anesthesia providers should consider all possible factors that could cause headaches in women who have undergone spinal anesthesia, regardless of age, BMI, blood sugar levels, blood pressure, immobilization time, or prior history of headaches.